Russia’s Pivot to Asia and Russia-Vietnam Economic Relations in the Early 21st Century - Bui Thi Huyen; Luu Van Quyet (Ital Publication, 2022)
Russia began to refocus its attention on the Asia-Pacific region in 1994, but the policy of pivoting toward Asia was implemented dramatically in the second decade of the 21st century. Adjustments made by Russia to its foreign policy and practical activities carried out by Russia in the region have impacted Russia-Vietnam relations generally and their economic ties in particular. Based on a qualitative approach and analysis of secondary data collected from previously conducted research works, this paper focuses on the following issues: (1) Adjustments made by Russia to its foreign policy towards Asia-Pacific over the first two decades of the 21st century; (2) Position of Vietnam in Russia’s foreign policy towards Asia–Pacific; and (3) Impacts of Russia’s new foreign policy on the economic ties between Russia and Vietnam over the first two decades of the 21st century. Based on the results of the analysis and evaluation, Russia's Asia-Pacific policy has been adjusted, particularly in the second decade of the 21stcentury, when the country turned its attention to Southeast Asia. Due to the importance of this region, Russia is implementing a comprehensive Asia policy and promoting Russia's interests in this region. The Russian Federation considers Vietnam an important partner in its